2014
DOI: 10.1186/1471-2229-14-103
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of WRKY family genes and their response to cold stress in Vitis vinifera

Abstract: BackgroundWRKY transcription factors are one of the largest families of transcriptional regulators in plants. WRKY genes are not only found to play significant roles in biotic and abiotic stress response, but also regulate growth and development. Grapevine (Vitis vinifera) production is largely limited by stressful climate conditions such as cold stress and the role of WRKY genes in the survival of grapevine under these conditions remains unknown.ResultsWe identified a total of 59 VvWRKYs from the V. vinifera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(108 citation statements)
references
References 72 publications
7
100
0
1
Order By: Relevance
“…Most SiWRKY genes were highly expressed in roots, whereas a few SiWRKY genes were expressed in developing seeds. This is consistent with observations made in other plants, including rice [18], cucumber [33], grape [42], apple [13], cassava [30], cotton [43], physic nut [41], and cabbage [44]. Our results revealed that SiWRKY genes are expressed tissuespecifically and the high expression levels observed in roots might reflect their roles in responses to abiotic and biotic stresses that first affect plants below ground.…”
Section: Diverse Expression Patterns Of Siwrky Genes In Different Tissupporting
confidence: 92%
“…Most SiWRKY genes were highly expressed in roots, whereas a few SiWRKY genes were expressed in developing seeds. This is consistent with observations made in other plants, including rice [18], cucumber [33], grape [42], apple [13], cassava [30], cotton [43], physic nut [41], and cabbage [44]. Our results revealed that SiWRKY genes are expressed tissuespecifically and the high expression levels observed in roots might reflect their roles in responses to abiotic and biotic stresses that first affect plants below ground.…”
Section: Diverse Expression Patterns Of Siwrky Genes In Different Tissupporting
confidence: 92%
“…As shown in Figs.2 and 3, 77 CitsWRKY proteins were classified into three main groups. This is consistent with the classification of WRKY family members in A. thaliana (Eulgem et al, 2000), O. sativa (Ross et al, 2007), Z. mays , and V. vinifera (Wang et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Structural diversity provides additional evidence of phylogenetic groupings, besides evolutionary information, for multigene families in which the gain or loss of an exon/intron can result from rearrangements and/or fusions of different chromosomal regions (Wang et al, 2014). The most closely related members of the same group, in general, showed the same standard exon/intron structure, such as number, position, and size of intron.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A diversidade estrutural fornece evidências adicionais aos agrupamentos filogenéticos, além de informações evolutivas das famílias multigênicas, no qual o ganho ou perda de um exon/íntron pode ser causada por rearranjos e/ou fusões de diferentes porções dos cromossomos (WANG et al, 2014). O padrão de distribuição dos íntrons/exons dos genes que fazem parte da assimilação de N em milho é mostrado na Figura 2.…”
Section: Figuraunclassified